The Da Vinci Code - Brown, Dan (London Corgi Books, 2004)
Police the murder of the curator of the Louvre are baffled by the prinvestigating escence of a series of codes left alongside the body - They are stunned to find that the clues lead back in history to the works of Leonardo Da Vinci and a centuries-old secret society.
Keywords: Dan Brown -- The Da Vinci Code -- Litrature